Investigating the Selectivity of KcsA Channel by an Image Charge Solvation Method (ICSM) in Molecular Dynamics Simulations (Communications in Computational Physics, 2018)
In this paper, we study the selectivity of the potassium channel KcsA by arecently developed image-charge solvation method (ICSM) combined with moleculardynamics simulations. The hybrid solvation model in the ICSM is able to demonstrateatomistically the function of the selectivity filter of the KcsA channel when potassiumand sodium ions are considered and their distributions inside the filter are simulated.Our study also shows that the reaction field effect, explicitly accounted for through image charge approximation in the ICSM model, is necessary in reproducing the correctselectivity property of the potassium channels.